Bone Marrow Necrosis - A rare clinicopathologic entity - Picture Question - Shah, Binay Kumar; Tretheway, David M (Journal of Advances in Internal Medicine, 2012)
DOI: http://dx.doi.org/10.3126/jaim.v1i1.5835 Journal of Advances in Internal Medicine. 2012; 1(1): 19